2011
DOI: 10.1007/s13239-011-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a Tissue-engineered Heart Valve from Human Fibroblasts Exhibiting Short Term Function in the Sheep Pulmonary Artery

Abstract: Abstract-We have previously demonstrated the feasibility of fabricating a fibrin-based tissue-engineered heart valve (TEHV) using neonatal human dermal fibroblasts (nhDF), including leaflets with structural and mechanical anisotropy similar to native leaflets. The aim here was to evaluate the performance of this TEHV in a pilot study using the sheep model. Bi-leaflet TEHV were conditioned in a cyclic stretching bioreactor, then implanted within a polymeric sleeve interpositionally into the pulmonary artery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…This phenomenon, which was also observed in TEHV based on other cell types [52,53], might be the result of the complete relaxation of the stent after harvest or of the relatively high amount of α-SMA. Elimination of cellular components (decellularization) of the TEHV might strongly reduce this problem, without altering the collagen structure or tissue strength [47].…”
Section: Discussionmentioning
confidence: 56%
“…This phenomenon, which was also observed in TEHV based on other cell types [52,53], might be the result of the complete relaxation of the stent after harvest or of the relatively high amount of α-SMA. Elimination of cellular components (decellularization) of the TEHV might strongly reduce this problem, without altering the collagen structure or tissue strength [47].…”
Section: Discussionmentioning
confidence: 56%
“…Recovery from CytoD and ROCK at 20% FBS occurred within 8 h and in vivo this will likely be faster due to higher serum concentrations. A recent study of Seydain et al confirms these expectations (Syedain et al 2011). They treated fibrinbased tissue engineered heart valves with blebbistatin before implantation to decrease retraction.…”
Section: Passive and Active Components In Tissue Retractionmentioning
confidence: 79%
“…However, there are still some challenges that need to be overcome. One of those challenges is cell-mediated leaflet retraction, causing regurgitation in vivo (Flanagan et al 2009;Gottlieb et al 2010;Syedain et al 2011). In general, this regurgitation has been neglected and reported to be only mild.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies on fibrin-based tissue-engineered heart valves 29,41 revealed an absence of thrombus formation, calcification, stenosis, or aneurysm development. This together with the excellent tissue remodelling shows the potential of TEHVs based on an autologous fibrin scaffold.…”
Section: Weber Et Almentioning
confidence: 99%
“…A confluent monolayer of endothelial cells was found on the whole valve surface 3 months after implantation 29 and extensive endothelialization was observed on the root lumen but not on the leaflet 8 weeks after implantation. 41 Flanagan and colleagues, differently from Syedain and coworkers, performed a short endothelialization process in vitro (30 min), but no efficiency of the process was reported. While it can be argued that sheep are able to endothelialize a variety of prostheses that are implanted in the circulation, 42 pericardial tissue valves were only partially covered with endothelial cells after 11 months in vivo in the sheep model.…”
Section: Weber Et Almentioning
confidence: 99%